Kompetencje użytkowników języka obcego. Wiedza socjokulturowa i kompetencja socjolingwistyczna studentów rusycystów - Janaszek, Krystyna (Studia Rossica Posnaniensia, 2021)
The paper describes the assumptions of modern methods of teaching foreign languages, and this description includes the proposals of their creators regarding the knowledge that the student must acquire and the competences that he/she is to form. The results of the test checking sociocultural knowledge and sociolinguistic competences of Russian Studies students is also discussed. The low global result of the test (57% of correct answers) showed a poor record of students in terms of the examined issues. Knowledge about Russia is very superficial among the study participants. They are also not good in dealing with contacts on the level of official relations (formal records of statements).